2020
DOI: 10.3389/fped.2020.00205
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathophysiological Insights Into Immunological Mediated Glomerular Diseases in Childhood

Abstract: The kidney is often the target of immune system dysregulation in the context of primary or systemic disease. In particular, the glomerulus represents the anatomical entity most frequently involved, generally as the expression of inflammatory cell invasion or circulant or in situ immune-complex deposition. Glomerulonephritis is the most common clinical and pathological manifestation of this involvement. There are no universally accepted classifications for glomerulonephritis. However, recent advances in our und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 214 publications
(242 reference statements)
0
20
0
1
Order By: Relevance
“…Cases of dual ANCA and anti-GBM antibody positivity are widely reported (17% of reported cases in children) and it has been suggested that the initial presence of ANCA may be the trigger responsible for exposing the epitope in the alpha-3 chain [8]. Dual positivity is associated with a poorer prognosis, and thus, early, aggressive treatment is recommended [18]. Patients may also present with features overlapping with membranous nephropathy at a higher rate than would be expected by chance and atypical presentations of this disease are reported [19].…”
Section: Overlap With Other Conditionsmentioning
confidence: 99%
“…Cases of dual ANCA and anti-GBM antibody positivity are widely reported (17% of reported cases in children) and it has been suggested that the initial presence of ANCA may be the trigger responsible for exposing the epitope in the alpha-3 chain [8]. Dual positivity is associated with a poorer prognosis, and thus, early, aggressive treatment is recommended [18]. Patients may also present with features overlapping with membranous nephropathy at a higher rate than would be expected by chance and atypical presentations of this disease are reported [19].…”
Section: Overlap With Other Conditionsmentioning
confidence: 99%
“…This final fibrous stage is unlikely to respond to immunosuppressive therapy and has a high risk of ESKD. 1,13,14 Types of Crescentic Glomerulonephritis: Three mechanisms of glomerular injury are known that can result in activation of podocytes and epithelial proliferation to form crescents. Type-I: Anti-GBM (Goodpasture syndrome)constitutes circulating antibodies IgG directed against the non-collagenous domain of alpha-3 chain of type IV collagen, present in the GBM and/or alveolar basement membrane.…”
Section: Post Infectious Gnmentioning
confidence: 99%
“…It accounts for 10%-15% of all diffuse crescentic GN and may present as GN alone or in combination with pulmonary hemorrhage (Goodpasture syndrome) and as ANCA associated "dual antibody disease". 14 Reported pediatric cases are very rare (n=31) with a higher prevalence in girls (M/F ratio 1:4). 15 Type-II: Immune complex mediated injury-Multiple stimuli lead to crescentic proliferative GN including infections, systemic diseases, and preexisting primary GN.…”
Section: Post Infectious Gnmentioning
confidence: 99%
See 2 more Smart Citations